Zintegrowane a dwuetapowe podejście do segmentacji w analizie conjoint - Kapłon, Robert (Integrated and two-stage approach to segmentation in conjoint analysis, 2006)
The segmentation of markets with conjoint analysis involves two-stage or integrated approach. In two-stage approach the estimation and the segmentation are performed separately. Conversely, if these two stages are combined then one calls it integrated approach. The aim of this paper is to compare these approaches. Except theoretical considerations the results of questionnaire investigation (concerning preferences in the market of cellular phones) are used in this comparison too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 406-414